2023
DOI: 10.14710/jpki.18.2.73-78
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Screen Time as The Most Influential Factor of Computer Vision Syndrome

Farhana Dhafira,
Riski Prihatningtias,
Trilaksana Nugroho
et al.

Abstract: Background: Since the Covid-19 Pandemic hit Indonesia, college students have had many eye health complaints; one is Computer Vision Syndrome (CVS). Factors that can increase the risk of CVS are decreased sleep quality, high computer/laptop use duration, and a non-ergonomic position. This study aimed to prove the relationship between sleep quality, visibility, and screen time on the incidence of CVS in medical students of Diponegoro University.Method: This cross-sectional study, including 147 medical students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[32], [33] In [34] Apparently, a study on sleep quality and screen time (the amount of time used by the eye to see the computer screen and mobile phone screen) also showed that it affects the incidence of computer vision syndrome (p = 0.001). [35] Based on several studies conducted, the family history of myopia also plays an essential role in the condition of visual acuity accompanied by activities related to the duration of gadget use (screen time), which can cause fatigue in the eye muscle and reduce the amount of sleep. [19], [36] Research in 2009, conducted on computer informatics engineering students analyzed the relationship between computer use and decreased visual acuity and revealed that there was a positive correlation of 32.1% between the two variables.…”
Section: Resultsmentioning
confidence: 99%
“…[32], [33] In [34] Apparently, a study on sleep quality and screen time (the amount of time used by the eye to see the computer screen and mobile phone screen) also showed that it affects the incidence of computer vision syndrome (p = 0.001). [35] Based on several studies conducted, the family history of myopia also plays an essential role in the condition of visual acuity accompanied by activities related to the duration of gadget use (screen time), which can cause fatigue in the eye muscle and reduce the amount of sleep. [19], [36] Research in 2009, conducted on computer informatics engineering students analyzed the relationship between computer use and decreased visual acuity and revealed that there was a positive correlation of 32.1% between the two variables.…”
Section: Resultsmentioning
confidence: 99%